If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6s + -11 = 51 + 5 Reorder the terms: -11 + 6s = 51 + 5 Combine like terms: 51 + 5 = 56 -11 + 6s = 56 Solving -11 + 6s = 56 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 6s = 56 + 11 Combine like terms: -11 + 11 = 0 0 + 6s = 56 + 11 6s = 56 + 11 Combine like terms: 56 + 11 = 67 6s = 67 Divide each side by '6'. s = 11.16666667 Simplifying s = 11.16666667
| 40-8x=-4(-6+3x) | | 48-8*3= | | (1x^2+7x-2)=0 | | 8s-12=24+5s | | 7(u-1)=4u+8 | | 48-8*2= | | 9(3x-2x)=2(10-8x) | | 7(y+9)=92 | | s-y=w | | 50-6*6= | | -5-6(3b+1)=39-8b | | -5x-6(x-5)=-x+30 | | 4(w+3)=8w | | 3x-11=x^2-9 | | D^2+8*d+9=0 | | 15-3*4= | | 4x^2-5=-5x+3 | | 3x+24y=9 | | -(8-4r)=-5+4r | | 24x^2+2xy-y^2=0 | | 23+5x=-2(x+6) | | 7(1+8v)+2v=7-6v | | 6(1-2x)-5=-83 | | 24x^2+2xr-r^2=0 | | 2x^3+x^2-19x+36=y | | -[2]=x-9 | | -2(v+3)=-18 | | x^2+1.68=2.6x | | 5(-4+m)=-45 | | 2x^3+x^2-19x+36=x | | -5r-3=-33 | | 6(4x+7)=105 |